(untitled) (Journal of Universal Science Research, 2023)
This article considers methodological component in the content of teaching the grammatical side of foreign language speech at the university. The goals of teaching a foreign language are an important methodological category. The starting point in determining the strategic goal of education is the social order of society in relation to the younger generation.